Frequency of Hepatitis B and Hepatitis C in Healthy blood donors of NWFP: A single center experience - Ahmad, Jawad; Taj, Abid Suhail; Rahim, Abdur; Shah, Afzal; Rehman, Muhammad (Journal of Postgraduate Medical Institute, 2011)
To determine the frequency of hepatitis B and C in asymptomatic healthy blood donors. A prospective study was conducted in the department of pathology, RMI Peshawar from April 2002 to March 2003. A total of 4000 healthy blood donors were selected. Blood samples were collected for screeening of HBs Ag and anti HCV antibodies using IMX or Axsym, MEIA technology (Abbott, USA).These results indicate that most of the patients suffering from hepatitis B and C do not realize that they have got such deadly viruses in their body and can transmit it to non infected healthy individuals via different parenteral routes including blood transfusion. Teh rate of infection of hepatitis B and C found in this study is low compared to other regional studies. One possible explanation could be the introduction of pre-donation filtration by questionaire method which has been found to be an effective tool in addition to routine virological screening using high quality standard methods.